Mengembangkan Kepariwisataan di Daerah Klaten - Alifiani Vedilla Putri; Calista Joy Priscilla (Institut Nalanda, 2023)
This journal discusses developing tourism in the Klaten area in learning Indonesian at Stiepar Yapari Aktripa in Bandung City. This research aims to find out how we as young people develop tourism in the Klaten area through today's young generation. This type of research is qualitative research with a naturalistic paradigm. As for the research instrument is the results of observations, interviews, and researchers as the key instrument. The data source for this research is the results of interviews with local residents, looking for additional information on the internet. The implementation of the concept of sustainable tourism is a challenge that continues to be realized, including in rural areas. The Klaten area is one of the areas that has tourism potential which offers water and cultural tourism attractions in the Klaten area. However, in its development there are still several obstacles such as inadequate facilities, community participation, and environmental issues. Therefore, it is appropriate that the concept of sustainable rural tourism development be conveyed to all stakeholders in Klaten Regency, especially the government and the community. The result is that the problems that occur are not only physical aspects but also social aspects and how to manage them. This aspect is closely related. Therefore we as young people must always pay attention to it.